Cooling‐Accelerated Nanowire‐Nitinol Hybrid Muscle for Versatile Prosthetic Hand and Biomimetic Retractable Claw. (29th December 2021) - Oh, Saewoong; Tabassian, Rassoul; Thangasamy, Pitchai; Mahato, Manmatha; Nguyen, Van Hiep; Nam, Sanghee; Huapeng, Zhang; Oh, Il‐Kwon
Abstract: As strong and shape‐conformable as biological muscles, nitinol shape memory alloys (SMAs) artificial muscles have great merit when applied for bio‐inspired robots. However, the low bandwidth and slow actuation speed of SMAs due to their sluggish cooling have long been troublesome, limiting possible applications. Here, to expedite the cooling rate, a Cu nanowire forest is directly grown on the surfaces of 3D shaped SMA coil (SMAc) to increase the surface area by 15 times and boost thermal convection. As a result, the Cu nanowire forest grown SMA coil (CuNF‐SMAc) shows accelerated cooling compared to bare SMAc (B‐SMAc): the actuation speed of CuNF‐SMAc is 100% faster than that of bare SMAc (B‐SMAc) under natural cooling and 170% faster under forced‐air cooling. With this faster actuation, CuNF‐SMAc artificial muscles are employed in a versatile prosthetic hand to bend and flex fingers. The proposed prosthetic hand successfully demonstrates a series of sign language within 4 s for each letter, and rhythmically plays a grand piano. Moreover, unique retractable feline claws are mimicked which demonstrate a fully tunable frictional force just like how cats do it, expanding the potential of a cooling‐accelerated SMAc artificial muscle. Abstract : The designed Cu nanowire grown shape memory alloy coil (CuNF‐SMAc) features facile thermal dissipation via a directly grown nanowire forest on the surface, thereby resolving the sluggish cooling of SMAc and widening its actuation bandwidth. Upon faster actuation, bundles of CuNF‐SMAc are successfully used as artificial muscles for a 3D printed versatile prosthetic hand and a biomimetic paw with a retractable claw.